2016
DOI: 10.1097/md.0000000000003455
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Instrumented Spinal Fusion on the Development of Vertebral Compression Fracture

Abstract: Instrumented spinal fusion has become one of the most common surgeries for patients with various spinal disorders. Only few studies have reported subsequent vertebral compression fractures (VCFs) after instrumented spinal fusion. The purpose of this study was to evaluate the risk of new VCFs in patients undergoing instrumented spinal fusion.We obtained claims data from the National Health Insurance Research Database of Taiwan and retrospectively reviewed 6949 patients with instrumented spinal fusion as the spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
0
13
1
Order By: Relevance
“…The influence of the dosage forms of alendronate sodium hydrate used here on the serum level of Ca may have been small despite its high efficacy in improving bone metabolism. In general, osteoporosis is frequently observed in females [30] . Therefore, we evaluated the changes of bone metabolism-related factors according to gender between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of the dosage forms of alendronate sodium hydrate used here on the serum level of Ca may have been small despite its high efficacy in improving bone metabolism. In general, osteoporosis is frequently observed in females [30] . Therefore, we evaluated the changes of bone metabolism-related factors according to gender between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that subsequent vertebral compression fractures occurred in 224 patients (11.6%). They also investigated subsequent vertebral compression fractures after instrumented spinal fusion surgery ( n = 6949) or non-fusion spinal surgery ( n = 69,490) from the National Health Insurance Research Database of Taiwan [13]. They reported that the incidences of developing subsequent vertebral compression fractures were 130 patients (1.87%) for instrumented spinal fusion surgery and 175 patients (0.25%) for non-fusion spinal surgery, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoporosis can directly affect the hold of the screws placed during surgery, especially when superimposed on pre-existing osteopenia and osteoporosis. This can lead to loosening of the screws, localized pain, screw pullout, and fractures at the interface between instrumented and non-instrumented levels [ 19 ]. The relative inactivity of the patients post spinal instrumentation has been documented to lead to increased loss of bone density.…”
Section: Discussionmentioning
confidence: 99%
“…The immobility of the fused stenotic spinal segment, with or without instrumentation, leads to restriction of lower lumbar motion, and a higher incidence of falls that can lead to VCF [ 8 ]. This appears to have a greater impact on the upper level of the fusion, and when combined with later development of osteoporosis, can lead to fractures close to the spinal fusion [ 19 - 20 ] (Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%